Assessment of delayed ventricular activation after myocardial infarction. (February 2019) - Valverde, Esteban R.; Arini, Pedro D.
Highlights: To carry out a comparative study between the standard SaECG technique and the non-invasive QRSSV index. To study the stable and/or unstable ventricular activation in patients with and without VT/VF, by using the QRSSV and SaECG techniques. To analyse the modulation of the QRSSV index during the healing and healed myocardial infarction phases. Abstract: Experimental and clinical studies have shown that after myocardial infarction (MI), increases the risk to develop cardiac arrhythmias. We have evaluated the ventricular activation during healing (MI7 ) and healed (MI60 ) stages after MI. We carried out a comparative study between the QRS spectral variance (QRS SV ) index and late potentials (LPs) obtained by the Signal-averaged (SaECG) technique. The electrocardiograms of 48 healthy subjects (C TRL ); 84 patients in MI7 and 41 in MI60 without VT/VF; and also 7 patients in MI7 and 6 in MI60 with VT/VF, were analysed utilizing the Frank leads. The QRS SV has increased ( p < 0.05) in patients without VT/VF for all leads during MI7 and MI60 with respect to C TRL, and just in a few leads in patients with VT/VF. Conversely, we have only found significant proportion of LPs in MI7 with respect to C TRL in patients with VT/VF and none without VT/VF. This investigation might help to comprehend the influence of time in patients with and without VT/VF. We conclude that SaECG could be restricted to locate stable and delayed depolarization, while the QRS SV index could detect both stable and unstable activation disorders in whole depolarization.